Response of rhizobium to spent engine-oil contamination in the rhizosphere of legumes (arachis hypogaea and phaseolus vulgaris) - Monday Ubogu; Ejiro Akponah; Ejovwokoghene Francis Ejukonemu (Kuwait Journal of Science)
Abstract